Preparation of titanium-doped indium oxide films by ultrasonic spray pyrolysis method - Surapong Panyata (2018)
Titanium-doped indium oxide (ITiO) films were deposited on soda-lime glass by ultrasonic spray pyrolysis. The optimum conditions of deposition parameters, such as dopant concentration for lowest resistivity were investigated. Phase formation and microstructure of the films were examined by XRD and SEM. AFM was used to obtain the surface topology of the prepared films. The optical transmission and resistivity of films were determined by UV-Vis-NIR spectrophotometer and Van der Pauw method respectively. The resistivity of films depended on the titanium content. The feasibility study of using the ITiO as one of the TCO for solar cell was discussed. © 2013 Copyright Taylor and Francis Group, LLC.